2019
DOI: 10.3390/insects10080238
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania and Trypanosoma DNA in Field-Caught Sand Flies from Endemic and Non-Endemic Areas of Leishmaniasis in Southern Thailand

Abstract: Phlebotomine sand flies are tiny, hairy, blood-sucking nematoceran insects that feed on a wide range of hosts. They are known as a principal vector of parasites, responsible for human and animal leishmaniasis worldwide. In Thailand, human autochthonous leishmaniasis and trypanosomiasis have been reported. However, information on the vectors for Leishmania and Trypanosoma in the country is still limited. Therefore, this study aims to detect Leishmania and Trypanosoma DNA in field-caught sand flies from endemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…In particular, Trypanosoma platydactyli was described in S. minuta [42], and the infection by a Trypanosoma belonging to Trypanosoma theileri group with very high homology to other trypanosomes detected in European cervids was recently reported in Phlebotomus perfiliewi [43]. In the Mediterranean area, Trypanosoma nabiasi, a rabbit trypanosome, and its co-infection with L. infantum was found in P. perniciosus female sand flies caught in the context of human leishmaniosis outbreak in Madrid [44], and natural infection of sand flies by trypanosomes of lizards, amphibians, birds and rodents has been already reported mainly from the American continent and Asia [45][46][47][48]. Despite Trypanosoma spp.…”
Section: Plos Onementioning
confidence: 81%
“…In particular, Trypanosoma platydactyli was described in S. minuta [42], and the infection by a Trypanosoma belonging to Trypanosoma theileri group with very high homology to other trypanosomes detected in European cervids was recently reported in Phlebotomus perfiliewi [43]. In the Mediterranean area, Trypanosoma nabiasi, a rabbit trypanosome, and its co-infection with L. infantum was found in P. perniciosus female sand flies caught in the context of human leishmaniosis outbreak in Madrid [44], and natural infection of sand flies by trypanosomes of lizards, amphibians, birds and rodents has been already reported mainly from the American continent and Asia [45][46][47][48]. Despite Trypanosoma spp.…”
Section: Plos Onementioning
confidence: 81%
“…Based on the morphological identification of female specimens, S. iyengari was the predominant species in several of the provinces investigated in this study, especially Chantaburi, Songkhla and Ubon Ratchathani provinces. The results of previous studies suggested that the species richness of sand flies in Thailand varied greatly among different provinces or habitats [ 19 , 32 – 36 ], possibly indicating that sand fly richness in Thailand might exhibit an area-specific distribution. These results indicated the need to investigate sand fly richness in several regions and habitats in order to obtain reliable information on sand fly species richness in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…These negative results suggest that more studies involving more traps per area need to be conducted with the aim to collect a large number of sand flies for more comprehensive investigation. In a previous study, sand flies collected in a leishmaniasis-free area of Thailand also exhibited negative results for Leishmania infection, whereas in a leishmaniasis-positive area, a low prevalence (0.45%) of Leishmania was detected [ 19 ]. In the future, an investigation of larger sand fly populations from several provinces and a variety of locations using massive molecular screening needs to be performed and possible reservoir hosts should be investigated in those areas; such studies will provide additional information on leishmaniasis transmission in Thailand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18S rRNA gene was chosen because previous analyses have demonstrated that this marker is adequate for phylogenetic differentiation of Trypanosoma species [ 40 ]. Multiple studies have used these primers to amplify Trypanosoma DNA from clades across the Trypanosoma phylogeny associated with mammals, sauropsids, amphibians, and fish [ 39 , 41 44 ]. A study by Hodo et al [ 45 ] was also able to amplify DNA from the related trypanosomatid genus Blastocrithidia in the blood of bats with these 18S rRNA primers.…”
Section: Methodsmentioning
confidence: 99%